Research on multi-objective optimization method for bullet full trajectory based on SA-PSO hybrid algorithm - HU Zhenchao, CUI Xiao, XU Xiao, LU Dabin, ZHANG Huisheng (Zhihui kongzhi yu fangzhen)
In the process of bullet design, the parameters of the interior trajectory, exterior trajectory, and terminal trajectory are interdependent, necessitating a comprehensive consideration of the entire trajectory process. To address both overall performance and design efficiency, a multi-objective optimization method based on simulated annealing and particle swarm optimization is proposed. A comprehensive ballistic calculation model is established, incorporating warhead characteristics, internal trajectory, aerodynamic parameters, external trajectory, and terminal trajectory. Twelve structural parameters are selected as optimization variables.The optimization objectives are set as travel distance, landing kinetic energy, and penetration thickness, facilitating comprehensive trajectory optimization.The weighted summation method is employed to ascertain the optimal solution,with the simulated annealing-particle swarm optimization (SA-PSO)utilized to address the optimization challenge. The results demonstrate that this approach converges to the optimal solution more efficiently compared to traditional algorithms. Compared to the original design, the optimized solution increases landing kinetic energy by 109.97%, enhances penetration thickness by 75.11%, and the travel distance is shortened by 30.01%. The proposed method significantly improves overall ballistic performance. Moreover, this method circumvents the decline in other objectives that commonly arises during the optimization of a single target.